FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU BERKENDARA AMAN (SAFETY RIDING) PADA KURIR POS SEPEDA MOTOR DI PT. POSINDONESIA CABANG ERLANGGA SEMARANG2017 - Septi Wulandari; Siswi Jayanti; Baju Widjasena (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Safety riding is a behavior in driving safely to prevent traffic accidents. Factors that can cause traffic accidents are driver, vehicle, road, and environment (weather). According to research's initial surveys, 61.1% courier admits that they have ever violated traffic rules and 33.3% have been in accidents while working. The purpose of this research is to analyze factors that affecting safety riding behavior on motorcycle courier in POS Indonesia at Erlangga, Semarang.The design of this research using quantitave research with cross sectional design study. The population of this research are 123 motorcycle couriers with 54 people as sample which using incidental sampling technique. Independent variable in this research are knowledge, attitude, motivation, driving experience period, availability of safety equipments, vehicle condition, the role of co-workers, and safety riding variable. This research using questionnaire. Statistical analysis is using Chi Square test. The result of this research shows that 42.6% couriers are driving recklessly and 57.4% couriers behave safely while driving. According to Chi Square analysis, variable that related to safety riding behavior are knowledge (p-value:0.054), attitude (p-value:0.007), motivation (p-value:0.000), and role of co-workers (p-value:0.016). Researcher suggest to gives safety riding training to increase courier's knowledge and skill and monitoring the properness condition of motorcycle.